New Urea Biosensor Based on Urease Enzyme Obtained from Helycobacter pylori - Dindar, Bahar; Karakus, Emine; Abasiyanik, Fatih (HUMANA PRESS INC, 2011)
The urease enzyme of Helicobacter pylori was isolated from biopsy sample obtained from antrum big curvature cell extracts. A new urea biosensor was prepared by immobilizing urease enzyme isolated from Helicobacter pylori on poly(vinylchloride) (PVC) ammonium membrane electrode by using nonactine as an ammonium ionophore. The effect of pH, buffer concentration, and temperature for the biosensor prepared with urease from H. pylori were obtained as 6.0, 5 mM, and 25 A degrees C, respectively. We also investigated urease concentration, stirring rate, and enzyme immobilization procedures in response to urea of the enzyme electrode. The linear working range of the biosensor extends from 1 x 10(-5) to 1 x 10(-2) M and they showed an apparent Nernstian response within this range. Urea enzyme electrodes prepared with urease enzymes obtained from H. pylori and Jack bean based on PVC membrane ammonium-selective electrode showed very good analytical parameters: high sensitivity, dynamic stability over 2 months with less decrease of sensitivity, response time 1-2 min. The analytical characteristics were investigated and were compared those of the urea biosensor prepared with urease enzyme isolated from Jack bean prepared at the same conditions. It was observed that rapid determinations of human serum urea amounts were also made possible with both biosensors.
Keywords: Helicobacter pylori; Urease enzyme; Isolation; Urea; Polyvinylchloride; Carboxylated polyvinylchloride; Palmitic acid; Nonactin; ION-SELECTIVE ELECTRODES; POTENTIOMETRIC BIOSENSOR; PVC MEMBRANE; HELICOBACTER-PYLORI; IMMOBILIZED ENZYME; BLOOD; SENSOR; SERUM; CREATININE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology